Minor proteins and enzymes of the Drosophila eggshell matrix. - Fakhouri, M.; Elalayli, M.; Sherling, D.; Hall, J.D.; Miller, E.; Sun, X.; Wells, L.; LeMosy, E.K. (Developmental Biology, 2006)
The Drosophila eggshell provides an in vivo model system for extracellular matrix assembly, in which programmed gene expression, cell migrations, extracellular protein trafficking, proteolytic processing, and cross-linking are all required to generate a multi-layered and regionally complex architecture. While abundant structural components of the eggshell are known and are being characterized, less is known about non-abundant structural, regulatory, and enzymatic components that are likely to play critical roles in eggshell assembly. We have used sensitive mass spectrometry-based analyses of fractionated eggshell matrices to validate six previously predicted eggshell proteins and to identify eleven novel components, and have characterized the expression patterns of many of their mRNAs. Among these are several putative structural or regulatory (non-enzymatic) proteins, most larger in mass than the major eggshell proteins and often showing preferential expression in follicle cells overlying specific structural features of the eggshell. Of particular note are the putative enzymes, some likely to be involved in matrix cross-linking (two yellow family members previously implicated in eggshell integrity, a heme peroxidase, and a small-molecule oxidoreductase) and others possibly involved in matrix proteolysis or adhesion (proteins related to cathepsins B and D). This work provides a framework for future molecular studies of eggshell assembly.